Perception of the Purwokerto Society on Meat Product - Muatip, K; Aunurohman, H (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2007)
Meat consumption has increased significantly due to improvement of wage and education level of people. Importation of meat was done to meet local demand that experienced a shortage because of low cattle production. Besides, negative issues on avian influenza and anthrax have become a barrier on cattle development. The aims of this research were to (1) know perception of the Purwokerto society on meat product (2) identity factors that are related to perception of the Purwokerto society on meat product. The research used survey method to families in Purwokerto. Samples of area were taken purposively and total of 25 persons were drawn randomly as respondents. Collected data were analyzed using Spearman Rank Correlation Coefficient Test to identity factors that are related to perception of the Purwokerto society on meat product. The results showed that perception of the Purwokerto society on meat product was moderate. Income was significantly correlated to perception of the Purwokerto society on meat product. (Animal Production 9(2): 111-115 (2007)Â Key Words : Perception, meat product, income